Analisis Kesalahan Siswa Dalam Memecahkan Masalah Matematika Menurut Polya Pada Materi Sistem Persamaan Linear Dua Variabel - Felisia Sunliani Lombo; Santje M. Salajang; Selfie L. Kumesan (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research uses the Polya problem-solving procedure to describe students' difficulty in problem-solving in the material about systems of linear equations in two variables. The method in this research is descriptive research. The subjects in this research were three students in Class VIII of SMP Negeri 6 Tondano. The data analysis techniques used are data presentation, data reduction and conclusion. The results of this research show that of the four stages of Polya problem solving, students who have the highest scores can fulfil all stages of Polya problem solving, students who have medium scores can fulfil three stages of Polya problem solving, and students who have high scores can fulfil two stages of Polya problem-solving.